2021
DOI: 10.1111/ctr.14429
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective evaluation of catheter ablation in atrial flutter post cardiac transplantation

Abstract: Background: Atrial flutter is the most common arrhythmia post cardiac transplantation. Observational studies in the non-transplant population have shown prognostic benefit with catheter ablation; however, there are no data in the heart transplant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Late-onset post-transplant AFL is a common complication late after HTX and plays an important role in the clinical management of HTX recipients [ 20 ]. Previous studies reported late-onset post-transplant AFL rates ranging from 8.0% to 11.5% [ 25 , 26 , 28 , 29 ]. Pavri and colleagues [ 28 ] published a late-onset post-transplant AFL rate of 8.0% (7 of 88) and Anselmino and colleagues [ 29 ] found a late-onset post-transplant AFL rate of 11.5% (42 of 364).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Late-onset post-transplant AFL is a common complication late after HTX and plays an important role in the clinical management of HTX recipients [ 20 ]. Previous studies reported late-onset post-transplant AFL rates ranging from 8.0% to 11.5% [ 25 , 26 , 28 , 29 ]. Pavri and colleagues [ 28 ] published a late-onset post-transplant AFL rate of 8.0% (7 of 88) and Anselmino and colleagues [ 29 ] found a late-onset post-transplant AFL rate of 11.5% (42 of 364).…”
Section: Discussionmentioning
confidence: 99%
“…While post-transplant atrial fibrillation often occurs in the early stage after HTX, atrial flutter (AFL) is a common atrial arrhythmia late after HTX [ 20 ]. The late onset of AFL after HTX may be the result of chronic changes caused by cardiac allograft vasculopathy and repeated graft rejection episodes [ 20 , 21 , 22 , 23 , 24 , 25 ]. Several authors have described an association between late-onset AFL after HTX and recurring episodes of graft rejection which can lead to myocardial damage including inflammation, edema, fibrosis and scar tissue resulting in cardiac remodeling as well as graft dysfunction [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations